Super (a, d)-Edge-Antimagic total labeling of subdivided stars and w-Trees - Javaid M.; Bhatti A.A. (Utilitas Mathematica, 2017)
Kotzig and Rosa (1970) conjectured that every tree is an edge-magic graph. Furthermore, Enomoto, Llado, Nakamigawa and Ringel (1998), proposed the conjecture that every tree admits a super (a,0)-edge-Antimagic total labeling. In this paper, we give support to the partial correctness of these conjectures by showing that subdivided stars and subdivided w-Trees are super (a,0)-edge-Antimagic total graphs. Also, we prove that these graphs are super (a,d)-edge-Antimagic total for some d ≠ 0.